2014
DOI: 10.1108/pm-02-2013-0009
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the determinants of rental housing satisfaction and considering moving in Finland

Abstract: Purpose – The purpose of this paper is to discuss the relation between dissatisfaction with housing conditions and considering moving among residents of Finnish rental multifamily buildings. The paper examines physical attributes, socioeconomic factors, and subjective opinions related to housing conditions and satisfaction with housing. Design/methodology/approach – Logistic regression analysis is used to examine survey data to analyse w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 21 publications
2
24
0
Order By: Relevance
“…This correlation, identified by the model, confirms the thesis widely reported in the literature about the ordinary importance of variable income in explaining the variations in residential property prices [18][19][20][21].…”
Section: Interpretation Of the Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…This correlation, identified by the model, confirms the thesis widely reported in the literature about the ordinary importance of variable income in explaining the variations in residential property prices [18][19][20][21].…”
Section: Interpretation Of the Resultssupporting
confidence: 74%
“…Potepan [19] has shown that household income and construction costs are the most important factors that influence housing prices in U.S. metropolitan areas. Gibler et al [20] have stressed, as regards the Finnish housing market, the predominance of income among the factors that have a positive influence on the decision to move house. Kryvobokov [21], comparing 81 regression models reported in the literature in order to determine, among the variables considered (demographic characteristics, income level of population, accessibility, planning and urban development characteristics, educational level of population, crime level, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In their study of Helsinki renters, Juntto et al () find the housing feature creating the most widespread dissatisfaction among residents is storage. Another study of Finnish tenants reports that 42% are very or fairly unsatisfied with the storage in their multifamily buildings (Gibler, Tyvimaa, and Kananen ).…”
Section: Discussionmentioning
confidence: 99%
“…Generally focused on single-family houses and commercial properties [20][21][22][23], hedonic price modelling has been mainly used to assess the effects of social, environmental, and urban characteristics on property values [24][25][26][27][28][29][30], pointing out the weight of urban amenities [31][32][33][34][35][36], environmental externalities [37][38][39][40], access services and neighborhood attributes [41][42][43][44][45], and energetic factors [46][47][48]. Other studies have highlighted the influence of socio-economic factors on the property price formation [49][50][51][52]. Sdino et al [53] have developed a pluri-parametric hedonic price model for the rapid assessment of a large real estate portfolio in various real estate market segments.…”
Section: Background On the Main Mass Appraisal Techniquesmentioning
confidence: 99%